Analysis of Revenue Recognition Based on PSAK Number 23: Case Study In Trading Company PT. Solusindo Ganda Kharisma - Lukmanul Hakim; W Wardokhi; Husnul Khotimah (Golden Ratio of Data in Summary, 2024)
This study aims to analyze the implementation of revenue recognition based on the Statement of Financial Accounting Standards (PSAK) No. 23 in the trading company PT. Solusindo Ganda Kharisma. In an increasingly competitive business environment, companies are required to implement an effective accounting information system to produce accurate and timely financial information. Revenue is one of the key elements in financial statements, where its recognition and measurement affect the quality of the information presented. This research uses a descriptive qualitative approach. Primary data were obtained through interviews with relevant parties in the company, while secondary data were sourced from the company’s financial statements, internal accounting policies, and other documents. The results of the study indicate that PT. Solusindo Ganda Kharisma has effectively implemented PSAK Number 23 in the recognition of revenue from the sale of goods and services. Revenue from the sale of goods is recognized when the goods have been received by the customer, while service revenue is recognized based on the percentage of work completion. However, several challenges remain, such as delayed revenue recognition due to late delivery of goods and discrepancies in estimating the percentage of work completion for service sales.